2006
DOI: 10.1097/01.pcc.0000192321.66637.e6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pediatric Risk of Mortality (PRISM) scoring in African children with falciparum malaria

Abstract: This discrepancy observed in five classes of expected mortality (Hosmer-Lemeshow chi-square test, p < .001) may have been due to chance (sample size too small for a valid test), to a lower standard of care in Dakar than in the American hospitals where PRISM was designed, or to a failure of PRISM to classify risk in severe malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
2
15
1
Order By: Relevance
“…Although some authors have shown that the PRISM score overestimated mortality13-16 and that it is not appropriate in specific pediatric populations, such as post‐trauma patients,34 patients with acute renal failure35 and related to Plasmodium falciparum malaria,36 in this study PRISM showed satisfactory discriminatory performance in differentiating survivors from non‐survivors, supporting the conclusion that higher PRISM scores are correlated with increased risk of death, similar other studies 7,10-12,27. …”
Section: Discussionsupporting
confidence: 84%
“…Although some authors have shown that the PRISM score overestimated mortality13-16 and that it is not appropriate in specific pediatric populations, such as post‐trauma patients,34 patients with acute renal failure35 and related to Plasmodium falciparum malaria,36 in this study PRISM showed satisfactory discriminatory performance in differentiating survivors from non‐survivors, supporting the conclusion that higher PRISM scores are correlated with increased risk of death, similar other studies 7,10-12,27. …”
Section: Discussionsupporting
confidence: 84%
“…Other published paediatric risk scores were evaluated in the FEAST derivation and validation datasets. PRISM III was developed in paediatric intensive care units in the USA and has been validated in a variety of settings [ 10 , 24 28 ]. The Bedside Pediatric Early Warning System score (PEWS) was developed in Canada to quantify severity of children in hospitalised children and help with referral to critical care experts [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…This could lead to misleading interpretations of severity and fatality rates [2,3,21,23-26,28]. In this series, the high lethality could be explained by the extreme severity of our cases, as reflected by the high frequency of MOD syndrome (91%), indisputable indications for resuscitation, and PRISM score in ventilated children (median PRISM h24 : 14, IQR: 10–19) twice as high as in our hospital's overall SM cases at the same period (median PRISM h24 : 7, IQR: 3–13), of which fatality rate was 12% [29,30]. However, the lethality in ventilated children was close to those seen in adults with malaria treated in ICU's [14-17,31].…”
Section: Discussionmentioning
confidence: 93%